2018
DOI: 10.1519/jsc.0000000000002735
|View full text |Cite
|
Sign up to set email alerts
|

Superior Training-Specific Adaptations With an 8-Week Yoak Push-up Training Program

Abstract: Lima, C, Li, Y, Low, JL, Herat, N, and Behm, DG. Superior training-specific adaptations with an 8-week yoak push-up training program. J Strength Cond Res 32(9): 2409-2418, 2018-There are few progressive metastability training programs in the literature. The purpose of this study was to investigate changes in strength, endurance, muscle activation, and neuromuscular efficiency after an 8-week progressive, push-up training program under stable and unstable conditions. Nineteen male and female recreationally trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…1), with an increase of 92 % at the final compared to the first training session. This is well in line with Lima et al [8] who found REPmax to increase by 82 % after 8 weeks of suspended pushup training performed to failure (1-3 sets/session, 2 sessions/ week). The increase in REPmax would be due to an improvement in muscle endurance and/or coordination, but mainly the former because the participants were well familiarized with the task before starting the training and REPmax kept increasing throughout the training period (▶ Fig.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…1), with an increase of 92 % at the final compared to the first training session. This is well in line with Lima et al [8] who found REPmax to increase by 82 % after 8 weeks of suspended pushup training performed to failure (1-3 sets/session, 2 sessions/ week). The increase in REPmax would be due to an improvement in muscle endurance and/or coordination, but mainly the former because the participants were well familiarized with the task before starting the training and REPmax kept increasing throughout the training period (▶ Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It is also reported that throwing velocity in female athletes (handballers and softballers) was significantly increased after a combination of 5-9 types of sling exercise training [9,10] but not after their traditional resistance training analogs [9] or regular (sport-specific) training [10]. A recent study by Lima et al [8] examined the effect of suspended push-up training performed alone (without other sling exercises) on muscle function, showing superior improvements over stable push-up training for muscle (push-…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations